Estimating Kinetic Rate Parameters for Enzymatic Degradation of Lyophilized Silk Fibroin Sponges - Jameson, Julie F.; Pacheco, Marisa O.; Butler, Jason E.; Stoppel, Whitney L. (Frontiers in Bioengineering and Biotechnology, 2021)
Sponge-like biomaterials formed from silk fibroin are advantageous as degradable materials in clinical applications due to controllable breakdown into simple amino acids or small peptides in vivo. Silk fibroin, isolated from Bombyx mori silkworm cocoons, can be used to form sponge-like materials where the mechanical and structural properties, including the elastic modulus, porosity and pore size, and level of nanocrystalline domains, or beta sheet structures, can be independently tuned during formulation resulting in a wide parameter space and set of final materials. To determine what parameters of the original lyophilized silk scaffold formulation drive in vivo degradation, we developed a kinetic model that examines the effect of initial scaffold conditions on the rate of degradation. To guide our kinetic model, we first measured in vitro degradation rates of silk sponges using common protein-degrading enzymes, Proteinase K and Protease XIV. The concentration of the enzyme in solution was varied (1 U/mL, 0.1 U/mL, 0.01 U/mL) along with the level of crystallinity within the sponge. Additionally, two methods of performing the degradation studies were explored: continuous method and discrete method. We held the silk concentration, polymer chain length and scaffold pore size constant during experimentation and kinetic parameter estimation. Experimentally, we observed that the enzyme itself and enzyme concentration within the bulk solution are the major components dictating silk sponge degradation under these conditions and thus sought to validate our kinetic model with these parameters in mind. Given that the silk fibroin biopolymer degradation evaluated here is by an enzymatic reaction, we aimed to fit experimental data with a Michaelis-Menten based kinetic model. Weighted, non-linear least squares analysis was used to determine the parameters from the data sets and Monte-Carlo simulations were utilized to obtain estimates of the error. We found that modified first order reaction kinetics, where the Michaelis-Menten constant, K_M, can be assumed to be much larger than the substrate concentration, explained the rate of degradation of lyophilized silk sponges and obtained first order-like rate constants. To our knowledge, these results represent the first investigations into determining kinetic parameters to understand and predict lyophilized silk sponge degradation rates.